Extroverted Personality Pattern Among Educational Guides - Mutashar Dayekh, khalaf (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Research problem: Many scholars dealt with subject of personality and its various and varieddimensions and its relationship to human behavior, positive and insulting, some of them see that it isrelated to individual's professional options, and some of them see that it is related to behavior ofpsychological individual and his psychological health, and some of them see that y are linked to humanform and narcissistic nature. One of mental health of psychological counselor is extent of itspsychological and social compatibility in institution in which it works, as individuals are different in theirbehavior according to different patterns of personalities, according to that difference, re are manyvariables that Extroverted patterns and nature of professional behavior such as innate preparations andbiological formations, and pattern of personality possess. And study of personality of educational guidesis an expression of interest in individual and society, and they have a fundamental role in building anddeveloping educational institutions and n society, so as much as guide is competent, knowledge andcreation that lies development and sophistication of nation, what this segment acquires from knowledgeand behavior is a basic factor in Creating process of promotion sought by society in its economic, socialand educational aspects. And Extroverted Personality is one of important variables that guide must showin his work and in his dealings with others, it is a standard and a stimulus for proper behavior, mentalhealth, and occupational success.